ORAL SQUAMOUS CELL CARCINOMAS: a literature review - Guedes, Cizelene do Carmo Faleiros Veloso (2021)
Squamous cell carcinoma (SCC) is considered a malignant neoplasm, which originates in the lining of the oral cavity and represents approximately 95% of malignant lesions in this area. The mortality rate related to oral OHC varies according to habits, socioeconomic aspects, quality of medical care received, preventive education, ethnicity, environmental factors and life expectancy. However, as the clinical evolution of this process does not always follow the expected clinicopathological criteria, new prognostic elements have been studied. It is usually located on the floor of the mouth and tongue. The objective of this study is to know about the epidemiology, risk factors, diagnosis and treatment, in order to detect and refer them early. The study is characterized as a narrative/conceptual review and a narrative bibliographic review was carried out, using material accessible to the general public, such as books and scientific articles, published in the last ten years through databases available on the internet. The study presents the main risk factors that can trigger HCC, including: smoking, alcoholism, diet, immunosuppression; hereditary factors and HPV infections. The study allowed us to verify the importance of an early diagnosis by the dentist to ensure adequate treatment, favorable prognosis and better quality of life for patients. It is concluded that accurate oral clinical examination is very important in all oral lesions, even if the main symptom is not focused on this point. For individuals who are at higher risk, a thorough examination should be performed and those who present suspicious lesions, referred for a specialized consultation.